Endothelial Cells Exhibit Two Waves of P-Selectin Surface Aggregation Under Endotoxic and Oxidative Conditions - Cabello-Verrugio, C (Springer Science and Business Media, LLC, 2019)
Sepsis is a clinical syndrome characterized by the presence of circulating microbial endotoxins and oxidative stress. Endotoxin and oxidative stress activate endothelial cells via a convergent signaling pathway (TLR4/MyD88/PI3 K/PLCɣ/NF-B) that stimulates both the transcription of SELP gene (which encodes for human P-selectin) and the release of P-selectin from Weibel–Palade bodies (WPBs). However, time course pattern of P-selectin surface aggregation has not been established in endothelial cells under 24 h of endotoxic or oxidative stress. Our study shows that P-selectin has at least two waves of aggregation at the cell surface: one 10 min and the other 12 h after endotoxic or oxidative stress. The first wave depends exclusively on WPB delivery to the cell membrane, while the second depends on P-selectin translation machinery, ER–Golgi sorting, and WPB surface delivery. Understanding adhesion molecule dynamics in endothelial cells could provide further molecular insights to develop diagnostic or therapeutic tools to aid in the management of sepsis. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.